Laccase enzyme immobilization on ferromagnetic support material for oil palm empty fruit bunches (OPEFB) pretreatment - Rashid, Shah Samiur; Huan, Hu Shian; Mohd Hasbi, Ab. Rahim; Sikder, Md. Belal Hossain; Sasi, Ahmed Abdulsalam H. (IOP Publishing, 2019)
Rapid development of oil palm industry causes a lot of environmental issues due to the large number of waste products such as OPEFB. OPEFB is rich in lignocellulose which can be hydrolyzed to product sustainable biofuel, an alternative sources of energy. The production of biofuel from lignocellulose waste requires pretreatment process to enhance efficiency of saccharification of the sugar content of the lignocellulose waste. Enzymatic pretreatment technique is more desirable as this technique does not generate greenhouse gas or any inhibitor that can interferes the saccharification process. Enzyme immobilization technique also involved to increase the stability of the enzyme and promote reutilization of the enzyme. In this study, laccase enzyme was immobilized on ferromagnetic particles to promote easy separation of the immobilized laccase enzymes from the reaction media. The result shows that laccase enzyme immobilized on the nickel particles which encapsulated with silica. 0.235 IU/g of immobilized laccase degraded 58 % of the lignin content in 0.5 g of OPEFB after 24 hours. Pretreated OPEFB increase the efficiency of saccharification by 161% in compare with the untreated OPEFB.